Polaron delocalization and transport in doped graphene nanoribbon thin films - Hermosilla-Palacios, M. Alejandra; Lindenthal, Sebastian; Earley, Justin D.; Aubry, Taylor J.; DeLuca, David; Al Khunaizi, Hashim; Spokoyny, Alexander M.; Zaumseil, Jana; Ferguson, Andrew J.; Blackburn, Jeffrey L. (ACS nano, 2025)
Graphene nanoribbons (GNRs) are quantum-confined π-conjugated monolayer semiconductors with attractive properties for optoelectronic applications. However, the ground- and excitedstate properties of charge carriers in GNRs are still poorly understood, particularly with regards to the coupling between charges and the GNR lattice and the degree to which this coupling impacts local and macroscopic charge transport. To address this issue, we systematically correlate carrier density-dependent charge transport with spectroscopic modulations in chemically doped thin films of armchair graphene nanoribbons (9-aGNRs). This study combines Fourier transform infrared (FTIR) and ultraviolet−visible−nearinfrared (UV−vis−NIR) spectroscopy with both local and macroscopic conductivity measurements to arrive at a full and self-consistent picture of transport in doped GNR thin films. Using three different molecular p-type dopants (i.e., oxidants), we demonstrate that hole polarons are the dominant quasi-particle determining charge transport in GNRs and that the degree of polaron delocalization depends sensitively on the dopant and the hole density. For all three dopants, the local conductivity probed by microwave spectroscopy substantially exceeds the longrange conductivity obtained by four-point probe measurements. Interestingly, the dopant size substantially influences charge transport at high hole densities. We ascribe this effect to different propensities for forming bipolarons with lower mobilities than polarons. Comparison of GNR transport and spectral properties to other prototypical π-conjugated semiconductors (e.g., semiconducting polymers or carbon nanotubes) benchmark the charge transport properties of GNR thin films for optoelectronic devices and applications.